Hybrid hard-decision iterative decoding of regular low-density parity-check codes - Zarrinkhat, P.; Banihashemi, A.H. (IEEE communications letters, 2004)
Hybrid decoding means to combine different iterative decoding algorithms with the aim of improving error performance or decoding complexity. In this work, we introduce "time-invariant" hybrid (H/sub TI/) algorithms, and using density evolution show that for regular low-density parity-check (LDPC) codes and binary message-passing algorithms, H/sub TI/ algorithms perform remarkably better than their constituent algorithms. We also show that compared to "switch-type" hybrid (H/sub ST/) algorithms, such as Gallager's algorithm B, where a comparable improvement is obtained by switching between different iterative decoding algorithms, H/sub TI/ algorithms are far less sensitive to channel conditions and thus can be practically more attractive.